Exhaled breath condensate pH determinants in school‐aged children: A population‐based study. Issue 7 (22nd June 2021) - Rama, Tiago Azenha; Paciência, Inês; Cavaleiro Rufo, João; Silva, Diana; Cunha, Pedro; Severo, Milton; Padrão, Patrícia; Moreira, Pedro; Delgado, Luís; Moreira, André
Abstract: Background: Exhaled breath condensate (EBC) pH is a promising biomarker of airway inflammation. Lack of method standardization and interstudy variability precludes its use in clinical practice. While endogenous determinants have been described, underlying mechanisms for variability are mostly unknown. Thus, we aimed to assess the association between asthma and EBC pH in children, while studying potential environmental factors for interstudy variability. Methods: A cross‐sectional analysis of exhaled breath condensates from 613 children, aged 7–12 years, was conducted. Assessments included lung function and airway reversibility, exhaled nitric oxide, allergic sensitization, and body mass index (BMI). Indoor air quality (IAQ) was assessed in children's classrooms during 5 school days. Post‐deaeration EBC pH showed a bimodal distribution, and the sample was split into acidic and alkaline groups. Regression models were constructed to assess the effects of asthma and asthma adjusted to IAQ parameters on EBC pH. Results: Following adjustment to gender and BMI, asthma was significantly associated with a lower EBC pH in the acidic group. The effect of asthma on EBC pH was independent of IAQ, in both groups. In the acidic group, EBC pH was significantly affected by temperature [ β  = −0.09 (−0.15, −0.02)] and PM 2.5 concentration [ β  = −0.16 (−0.32, −0.01)], and in the alkaline group by relative humidity [ β  = 0.07 (0.02, 0.13)] and concentration of endotoxins [ β  = −0.06 (−0.1, −0.01)]. Conclusion: Our study shows that in addition to individual determinants such as asthma, environmental factors may influence and should be taken into consideration when interpreting EBC pH level in children. Abstract : Exhaled breath condensate pH is a promising biomarker of asthma that may be influenced by air quality. As such, standardization on collection room air quality measures is needed.